2023
DOI: 10.54527/jdir.2023.42.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Long-term clinical outcomes of single short implants in the mandibular molar area

Abstract: Purpose: This retrospective study evaluated a long-term result of single short implants in the mandibular molar area. Materials and Methods:The patients enrolled in this study had received 7-and 8-mm single short implants between November 2005 and February 2014. The clinical results were analyzed according to the length of implants, including survival and success rates and marginal bone loss. The cumulative survival rates were measured using the Kaplan-Meier survival curves, the success rate was analyzed accor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Generally, implants with lengths ranging from 6 mm to 8 mm are referred to as short implants. Success rate of short implants is generally known to be comparable to that of longer implants 1,2) . Among short implants, ultra-short implants are those with lengths less than 6 mm.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, implants with lengths ranging from 6 mm to 8 mm are referred to as short implants. Success rate of short implants is generally known to be comparable to that of longer implants 1,2) . Among short implants, ultra-short implants are those with lengths less than 6 mm.…”
Section: Introductionmentioning
confidence: 99%
“…shown that short implants have high survival rates, with a low incidence of prosthetic and biological complications [11][12][13][14][15] . However, implant survival is a minimal crite- .…”
Section: Introductionmentioning
confidence: 99%